Improvement of the System of Strategic State Regulation in the Tourism Industry - BEKETOVA, Olga N.; FROLOV, Alexander L.; BELOUSOVA, Irina V.; DUDINA, Elena A.; POMINOVA, Alexandra I. (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019, 2020)
The article is devoted to the elaboration of approaches aimed to improve the system for strategic state regulation in the tourism industry. It has been established that promising areas for strategic state regulation can include the development of recreational and sanatorium-resort facilities, as well as the introduction of new research-intensive technologies of recreation, treatment, rehabilitation, services, professional training of personnel and measures to make the management of the recreational industry more efficient. The authors propose to direct recreational policy to the efforts to provide environmental security during the recreational development of an area and to determine certain zones of recreational areas with the detachment of developed, promising and reserve areas. It has been proven that strategic state regulation is based on strategic state planning, which can be understood as management corresponding to specified long-term goals and objectives set to develop the country as a whole and its separate regions from the socio-economic point of view.